An analysis of the economic torts - Carty, Hazel (Oxford : Oxford University Press, 2010)
Economic torts are an area under-theorised and sparsely explored. Hazel Carty cuts through the resulting chaos to provide practical legal research to analyse the ingredients uncertainties, and possibilities of the economic torts, and to suggest a coherent framework for their future development.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Torts -- Economic aspects -- Great Britain; Competition, Unfair -- Great Britain